2018
DOI: 10.1016/j.jfda.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carnosic acid in Rosmarinus officinalis L. using square wave voltammetry and electrochemical behavior

Abstract: A new, fast, sensitive and simple voltammetric method is established for the direct determination of carnosic acid (CA). And the electroreduction of carnosic acid (CA) was studied using electrochemical methods. The number of electrons transferred in electrode mechanisms were calculated for reversible and adsorption-controlled electrochemical reduction of CA at 17 mV versus Ag/AgCl at pH 7.0 in Britton-Robinson buffer (BR) on a hanging mercury drop electrode. Square-wave voltammetry was developed and validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Yilmaz et al studied the electrochemical behavior of carnosic acid and based on their findings, developed a square-wave voltammetric method for the determination of carnosic acid in rosemary extracts. This method displayed good linear responses and the results are in good agreement with an HPLC-UV method [99].…”
Section: Capillary Electrophoresis (Ce) and Other Techniquessupporting
confidence: 65%
See 1 more Smart Citation
“…Yilmaz et al studied the electrochemical behavior of carnosic acid and based on their findings, developed a square-wave voltammetric method for the determination of carnosic acid in rosemary extracts. This method displayed good linear responses and the results are in good agreement with an HPLC-UV method [99].…”
Section: Capillary Electrophoresis (Ce) and Other Techniquessupporting
confidence: 65%
“…Two less-explored techniques that were applied for the analysis of diterpenes such as carnosic acid are UV spectrophotometry and square-wave voltammetry (SWV) [98,99]. The former was utilized for the quantitative determination of the diterpenes extracted from garden sage leaves.…”
Section: Capillary Electrophoresis (Ce) and Other Techniquesmentioning
confidence: 99%
“…For RE, the smaller oxidation current and broader peak are likely a result of competing reversible oxidation–reduction currents due to the different species that comprise rosemary extract. It has been shown that both carnosic and rosmarinic acid, which are the primary components of rosemary extract, produce reversible electrochemical properties when subjected to anodic and cathodic currents. , BHT also shows a smaller current and a wider peak than sesamol, along with a broader decay slope, which could be partially due to the steric hindrance of BHT and sesamol.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that both carnosic and rosmarinic acid, which are the primary components of rosemary extract, produce reversible electrochemical properties when subjected to anodic and cathodic currents. 29,30 BHT also shows a smaller current and a wider peak than sesamol, along with a broader decay slope, which could be partially due to the steric hindrance of BHT and sesamol.…”
Section: Determining Figures Of Merit Formentioning
confidence: 96%